Correlates of Criminal Behavior: Fatima Fatima - Fatima Fatima (International Journal for Electronic Crime Investigation, 2021)
This review paper traces the ardently debated correlates of criminal behavior and its associated factors. A short overview of crime and criminality has been discussed. The systematic relationship of crime and criminal behavior is enlightened that how certain factors within a system including ecological, macro-level or social, and micro-level or individual factors affect an individual personality that eventually will contribute to criminal acts such as robbery, homicide, child abuse, sexual assault, etc. Emphasis on different mechanisms established between individual and environmental factors settled during life developing process has been reviewed that may cause a crime to occur. Positive or negative correlations between crime and other factors such as biological, religiosity, political, and psychological factors have been observed. The findings of these correlates on an individual and society exposed outcomes of crime and criminal activity.